Análise quali-quantitativa dos Sciaenidae na pesca do camarão sete-barbas (Xiphopenaeus kroyeri), litoral de Santa Catarina Brasil - Monteiro, Herbert Silva (Universidade Federal de São Carlos, 2014)
Trawling with network-of-doors practiced by the artisanal fleet directed to-bobshrimp Xiphopenaeus kroyeri in central and northern coast of Santa Catarina is an efficient way to capture the target species. However, it has low selectivity and incidentally capture large contingent of demersal and benthic fauna, grouped on the designation of bycatch species, part of this is compounded by the Sciaenidae comprising teleost fish with great commercial importance. Based on this finding, the aim of this work was to evaluate qualitative and quantitative fish species present in the Sciaenidae accompanying fauna in three traditional areas of fishing-bob-shrimp. Seasonally, during the day, from September 2009 to July 2010, drags on traditional shrimp fishing areas in the municipalities of Bal. Barra South and Porto Belo, Santa Catarina, and monthly hauls were performed during the period September 2011 to August 2012 at easel Itapocoroy Penha, Santa Catarina. It appears that the composition of the Sciaenidae of accompanying fauna is dominated by demersal fish, belonging to two genera and three species Stellifer rastrifer, and S. brasiliensis Paralonchurus brasiliensis characterized dominant. The populations show seasonal fluctuations in abundance, with the highest catch rates in summer and lowest in winter. In general, the populations of the three species showed similar results in the evaluated parameters, experiencing a dominance of males in relation to females throughout the sampling period, with a predominance of males in the smaller length classes and the larger female. As the size of the first maturation of these species of approximately 9cm with the occurrence of two clutches per year. Trawling with network-of-doors practiced by the artisanal fleet operates intensely on juvenile population despite large share of the adult population.
Keywords: Peixe; Sciaenidae; Ictiofauna; Pesca artesanal; Ichthyofauna; Trawling with nets port; CIENCIAS BIOLOGICAS::ECOLOGIA